1942
DOI: 10.1172/jci101296
|View full text |Cite
|
Sign up to set email alerts
|

The Urinary Excretion of Thiamine as an Index of the Nutritional Level: Assessment of the Value of a Test Dose

Abstract: Harris and Leong (1), in 1936, suggested that the state of vitamin B1 deficiency in man could be detected by measurement of the amount of the vitamin excreted in the urine in the twenty-fourhour period following a single oral test dose of 900 micrograms of thiamine chloride, and since then many other procedures have been suggested for the detection of vitamin B1 deficiency by means of a test dose (2 to 8). Oral and parenteral routes have been used for administration of test doses varying from 1 to 10 mgm. of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1942
1942
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Boric acid (3 g) was added to the containers as a urine preservative. In earlier studies, highly corrosive acids had been used as preservatives, that is glacial acetic acid (Mason and Williams, 1942;Mickelsen et al, 1947;Levy and Hewitt, 1971), concentrated hydrochloric acid (Sauberlich et al, 1979), concentrated sulphuric acid (Ziporin et al, 1965), to maintain urine pH below 4 to ensure thiamine stability (ICNND, 1963). However, thiamine is known to be stable in mildly acidic conditions, but becomes unstable and easily destructed at pH 8 or above, especially at high temperatures (Brody, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boric acid (3 g) was added to the containers as a urine preservative. In earlier studies, highly corrosive acids had been used as preservatives, that is glacial acetic acid (Mason and Williams, 1942;Mickelsen et al, 1947;Levy and Hewitt, 1971), concentrated hydrochloric acid (Sauberlich et al, 1979), concentrated sulphuric acid (Ziporin et al, 1965), to maintain urine pH below 4 to ensure thiamine stability (ICNND, 1963). However, thiamine is known to be stable in mildly acidic conditions, but becomes unstable and easily destructed at pH 8 or above, especially at high temperatures (Brody, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…For example in the United Kingdom, there are only about 4% of missing values for thiamine food composition database, most of them in the group of soups, sauces, herbs and spices, none of them particularly rich sources of thiamine (Food Standards Agency and Research, 2002). Thiamine balance studies have demonstrated that the amounts recovered in the urine exhibit a close relationship with intake (Mason and Williams, 1942;Mickelsen et al, 1947;Sauberlich et al, 1979). However, in these studies, the differences in thiamine intake were achieved by administration of thiamine supplements and not by food.…”
Section: Introductionmentioning
confidence: 99%
“…For adults, excretion of less than 100 mcg/day thiamine in urine suggests insufficient thiamine intake, and less than 40 mcg/day indicates an extremely low intake. 16 In studies that examined thiamine status in patients with AD, the TPP effect on transketolase in blood was significantly higher (12%) in AD than controls, 14 and thiamine in plasma is reduced by about one-third in AD patients. 17 These measures suggest that a significant portion of AD patients are thiamine deficient.…”
Section: Thiamine-dependent Processes Are Diminished In Patients With Admentioning
confidence: 98%
“…Another commonly used measure of thiamine status is urinary thiamine excretion, which provides data on dietary intakes but not tissue stores. For adults, excretion of less than 100 mcg/day thiamine in urine suggests insufficient thiamine intake, and less than 40 mcg/day indicates an extremely low intake . In studies that examined thiamine status in patients with AD, the TPP effect on transketolase in blood was significantly higher (12%) in AD than controls, and thiamine in plasma is reduced by about one‐third in AD patients .…”
Section: Thiamine‐dependent Processes Are Diminished In Patients With Admentioning
confidence: 99%
“…In sick patients, evaluation of similar slight changes is complicated by the knowledge that physiologic variations, of the type exhibited in passing from the fasting to the absorptive state, may affect thiamin excretion as much as deficiency itself (16,17). It is evident, therefore, that while excretion may be correlated with tissue concentrations under standard conditions (18), it is also unfortunately dependent upon renal function (3) and upon a number of variables which affect the rate at which thiamin is absorbed and distributed to the tissues, and the rate at which the tissues in turn can phosphorylate the vitamin, bind it to their protein (19), or destroy it. Control of these variables constitutes a major difficulty in the clinical application of tolerance tests.…”
Section: Methods a Tissue Analysesmentioning
confidence: 99%